Contribution of Islamic Religious Education Teachers in the Process of Implementing the Independent Learning Curriculum - Widia Ningsih; Imam Syafei; Erjati Abbas (Edumaspul: Jurnal Pendidikan, 2024)
teachers in implementing the independent learning curriculum. The aim of the research is to explore the contribution of Islamic Religious Education teachers in implementing the Independent Learning Curriculum at Madrasah Aliyah Negeri 1 Tanjungkarang, Bandar Lampung. The field study method was used with observation, interviews and documentation techniques. The research subjects consisted of the principal and two Islamic Religious Education teachers. The results show that teachers have an important role in shaping student character, promoting tolerance, and integrating Islamic values. Despite facing challenges such as limited resources and resistance to change, with the right support, they can play a significant role in realizing the vision of the Independent Learning Curriculum. The conclusion emphasizes the importance of their role in education oriented to Islamic values. Recommendations include a good understanding of curriculum principles and innovative learning approaches, as well as appropriate training for teachers and adequate support from school principals.